Smart water-powered renewable energy system with IoT integration - Ahmed, Amjed Abbas; Najim, Ali Hamza; Ibraheem, Ahmed Salman; Ali Alheeti, Khattab M.; Mohd Satar, Nurhizam Safie; Hassan Abdalla Hashim, Aisha (IEEE Xplore, 2024)
An advanced hybrid renewable energy collecting and storage system prototype that utilizes water flow as its primary power source. Additionally, the system incorporates an energy monitoring system based on the Internet of Things (IoT) technology. The device effectively harnesses energy from the movement of water, storing it for future use in low-voltage applications. It demonstrates a maximum daily energy capture capacity of about 100Wh. The energy monitoring system, based on the Internet of Things(IoT), enables the real-time and remote monitoring of energy harvesting and usage. We thoroughly assessed the energy harvesting component across different situations to identify the crucial parameters that impact energy output. The results of our study demonstrate that several elements, including the spatial separation “between the energy harvester and the water source, Water flow” speed, sensor orientation, and sensor density, all play significant roles in determining the quantity of energy collected. This research shows that it is possible to integrate IoT technology with hydropower renewable energy systems. It provides significant perspectives on enhancing energy extraction efficiency in practical scenarios.